RESULTS OF A STUDY OF CLINICAL AND NEUROPHYSIOLOGICAL CHANGES IN PATIENTS WITH POST-TRAUMATIC EPILEPSY WITH CONCOMITANT SOMATIC DISEASES ON THE BASIS OF COMPLEX DRUG THERAPY (World Bulletin of Public Health, 2022)
The etiological role of mild traumatic brain injury in the genesis of the disease has not been definitively established; the prognosis of posttraumatic epilepsy after trauma and the feasibility of preventive therapy with antiepileptic drugs (AEDs) in these patients to reduce the risk of the disease remain unresolved. The informative value of new highly sensitive electrophysiological (video-eEG monitoring) and neuroimaging (magnetic resonance spectroscopy and positron emission tomography) instrumental studies in diagnosing the disease and indications for their use have not been established. The efficacy of combination therapy with antiepileptic and neuroprotective drugs has not been studied. This is the cause of late diagnosis and untimely treatment in patients with post-traumatic epilepsy. As a result, the number of patients with pharmacoresistant course of the disease, personality changes, intellectual and mental disorders, social disadaptation, sharp deterioration in quality of life increases significantly. All of the above suggests. the relevance of this study, which provides for the improvement of diagnosis and drug treatment of posttraumatic epilepsy.
Keywords: Epilepsy; seizures; epileptic status; trauma